1995
DOI: 10.1002/crat.2170300828
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dopant Distributions in LEC‐InP

Abstract: It is often important to be able to estimate the concentration of dopant atoms incorporated into InP crystals grown from InP melt of given composition. In this paper we present a simple parameter (G) to revise the commonly used effective distribution coefficient (kerf) and the Scheil equation. The results obtained for various dopants and different initial concentrations in LEC-grown InP ingots are discussed. It is shown that the revised dopant concentration curves tally with the real distributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…It should be noted that apparently the low pulling rate used in the growth of 161 (3 mm h −1 ) leads to a lower segregation coefficient with respect to the crystals grown at 8-15 mm h −1 . This evidence validates previous estimates based on electrical measurements [3] and also confirms the conclusions of Wei [2], who estimated the distribution coefficient of Fe in InP to be 0.0016, empirically decreased by 30-45% in order to match the real Fe distribution in crystals grown under different conditions. Our present results qualitatively agree also with the theory proposed by Burton, Prim and Slichter (BPS) according to which the effective distribution coefficient of any impurity during melt growth depends on the 'true' distribution coefficient K at the solid/liquid interface according to a well known relationship (…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It should be noted that apparently the low pulling rate used in the growth of 161 (3 mm h −1 ) leads to a lower segregation coefficient with respect to the crystals grown at 8-15 mm h −1 . This evidence validates previous estimates based on electrical measurements [3] and also confirms the conclusions of Wei [2], who estimated the distribution coefficient of Fe in InP to be 0.0016, empirically decreased by 30-45% in order to match the real Fe distribution in crystals grown under different conditions. Our present results qualitatively agree also with the theory proposed by Burton, Prim and Slichter (BPS) according to which the effective distribution coefficient of any impurity during melt growth depends on the 'true' distribution coefficient K at the solid/liquid interface according to a well known relationship (…”
Section: Resultssupporting
confidence: 91%
“…However, due to the very small distribution coefficient, a large Fe concentration gradient exists between top and tail of the crystals, which limits the optimal compensation ratio to a relatively small fraction of the LEC crystals. The problem of Fe segregation has already been discussed in many papers [1][2][3][4][5][6][7][8][9]; however no clear correlation has so far been established between growth parameters, distribution coefficient and electrical activity of Fe in bulk LEC InP. In previous papers the effect of different growth parameters, such as pulling rate and rotational speeds, on the distribution coefficient of iron were studied [3] and some hypotheses about the electrical activity of iron in LEC InP were advanced [4].…”
Section: Introductionmentioning
confidence: 99%
“…As pointed out in [11], it is interesting to note that the higher the pulling rate the higher the distribution coefficient. This is in agreement with the BPS theory [13] and with the experimental findings of Wei [5] and Fornari et al [6]. Figure 1(a), (b) also contains the concentrations of active iron, Fe active = Fe I n [14,15], measured by optical absorption measurements at 1 µm.…”
Section: Survey Of Experimental Datasupporting
confidence: 89%
“…a concentration gradient between top and bottom of the crystals, which limits the optimal compensation ratio to a relatively small fraction of the LEC ingots. The problem of Fe segregation has already been discussed by different authors [3,[5][6][7][8][9][10], and it appears that there is a complex correlation between growth parameters, distribution coefficient and electrical activity of Fe in bulk LEC InP. For instance, it was reported that the pulling rate and rotational speeds affect the Fe distribution coefficient [6] as well as the electrical activity of iron in LEC InP [7].…”
Section: Introductionmentioning
confidence: 97%
“…Table 4.3 lists the main dopants used for control of electrical and dislocation properties. The effective segregation coefficient for each impurity is also listed [27,28]. This gives some indication of the axial nonuniformity that can be expected in the electrical behaviour in normal directional growth.…”
Section: Crystal-growth Modellingmentioning
confidence: 99%